"No one may starve in the British Empire": Kwashiorkor, Protein and the Politics of Nutrition Between Britain and Africa. (4th November 2019) - Nott, John
Summary: Throughout the twentieth century it was widely assumed that African diets were grossly deficient in protein, that childhood protein deficiency was a natural result of this generalised diet and that a relative lack of meat and milk went some way to explaining African economic underdevelopment. This article explores why these conclusions took hold; the European deification of animal protein in previous centuries; structural changes to African diets and food economies under colonial government; and the political value of such a consensus. Unlike elsewhere in the world, where deficiency was removed from the exceptionalism of tropical medicine, protein malnutrition was constructed as a particularly African concern. Focusing this discussion on the history of the severe childhood deficiency, kwashiorkor, this article explores how the politically informed othering of African nutrition came to direct, or misdirect, the medicine of malnutrition in twentieth-century Africa.